Reactor Comparison for the Esterification of Fatty Acids from Waste Cooking Oil - Mazubert, Alex; Crockatt, Marc; Poux, Martine; Aubin, Joelle; Roelands, Mark (Chemical engineering & technology, 2015)
Esterification of the fatty acids contained in waste cooking oil with glycerol, a reaction involving immiscible and viscous reactants, was achieved in two pilot‐scale continuous pulsed reactors: the oscillatory baffled reactor and the helix reactor. In both reactors, with or without baffles, the reaction reaches its thermodynamic equilibrium at lower temperatures, shorter residence times and with higher selectivities than those reported in the literature. This equilibrium is then shifted by an increase in the excess of glycerol, or by removing water from the reactive media by an intermediary decantation or by the use of dodecylbenzene sulfonic acid, a surfactant catalyst. Further investigations would be required to increase the conversions without decreasing the selectivities, by increasing the initial amount of free fatty acids. The esterification reaction of the fatty acids contained in waste cooking oil (40 % of free fatty acids) with glycerol was carried out by two continuous and intensified technologies: an oscillatory baffled reactor and a pulsed helix reactor. Good conversions and selectivities were obtained at lower temperatures and shorter residence times than in conventional reactors.